Epidemiology of HCV infection in the Central European region - Urbánek, Petr; Kristian, Pavol; Makara, Michael; Hunyady, Bela; Tomasiewicz, Krzysztof (Clinical and Experimental Hepatology, 2016)
Opinion leaders in each of four countries in the Central European region summarize the available data on hepatitis C virus (HCV) epidemiology. The overall prevalence of anti-HCV antibody reactivity in this region varies between 0.2% and 2.1%, the most prevalent HCV genotype is GT 1. The commonest route of transmission is intravenous drug abuse at present.